Differential Associations of Diastolic and Systolic Pressures With Cerebral Measures in Older Individuals With Mild Cognitive Impairment - Shokouhi, Mahsa (Am J Hypertens, 2018)
BACKGROUND: Reports on the relative importance of the diastolic and systolic blood pressures (DBP and SBP) in age-related cognitive decline are mixed. Investigating the relation between DBP/SBP and functional and structural brain changes could elucidate which of the 2 measures is more critically important for brain function and, consequently, cognitive impairment. METHODS: We investigated the association of SBP and DBP with cortical volume, cerebral blood flow (CBF), and white matter lesions (WML), in nondemented older adults with and without mild cognitive impairment (MCI; N = 265, 185 MCI, mean age = 64 years). Brachial blood pressure was measured twice while seated, and the average of the 2 measures was used. Cortical volume, gray matter (GM) CBF, and WML were estimated using T1-weighted imaging, arterial spin labeling, and fluid attenuation inversion recovery, respectively. RESULTS: Reduced cortical volume was associated with elevated DBP (β= −0.18, P = 0.034) but not with SBP (β = −0.10, P = 0.206). GM CBF was associated with DBP (β = −0.13, P = 0.048) but not with SBP (β = −0.07, P = 0.275). Likewise, CBF within brain regions where MCI patients showed hypoperfusion were only associated with DBP (DBP: β = −0.17, P = 0.005; SBP: β = −0.09, P = 0.120). WML volume was associated with both DBP (β = 0.20, P = 0.005) and SBP (β = 0.30, P < 0.001). For all measures, there was no interaction between DBP/SBP and cognitive status, indicating that these associations were independent of the cognitive status. CONCLUSIONS: Independently of the cognitive status, DBP is more critically important for GM volume and perfusion, whereas WML is associated with both blood pressures, likely reflecting long-term effect of hypertension and autoregulation dysfunction.